Vitamin B12 Deficiency and West Syndrome: An Uncommon but Preventable Cause of Neurological Disorder. Report on Three Cases, One of Them with Late Onset during Vitamin B12 Treatment - Pavone, Piero; Sullo, Federica; Falsaperla, Raffaele; Greco, Filippo; Crespo, Agustina; Calvo, Agustin; Caraballo, Roberto (Neuropediatrics, 2021)
Vitamin B12 is a water-soluble vitamin that plays a fundamental role as an essential cofactor for two enzymes responsible for the production of succinyl-CoA and methionine. Vitamin B12 deficiency can occur in infants and may be related to the breastfeeding mother's adherence to a vegan diet or somatic diseases in the mother. It should be differentiated from inborn errors of vitamin B12 metabolism. Herein, we report the cases of three infants with West syndrome; all three were breastfed by mothers who followed a strict vegan diet. In one of the three infants, West syndrome developed during treatment with vitamin B12 and normalization of the vitamin B12 level. Early treatment and replacement therapy are worthwhile to prevent serious neurological problems and to improve the patient's clinical course.
Keywords: West syndrome; vitamin B12; epileptic encephalopathy